Bladder-related quality of life in people with neurological disorders: reliability and validity of the Turkish version of the King’s Health Questionnaire in people with spinal cord injury - Karapolat, Hale (Turk J Urol, 2018)
OBJECTIVE: To assess the validity and reliability of the Turkish version of the King’s Health Questionnaire (KHQ) in patients with spinal cord injury (SCI) and to compare the bladder- related quality of life between patients with SCI and multiple sclerosis (MS). MATERIAL AND METHODS: Thirty-five patients with SCI and 57 patients with multiple sclerosis (MS) were included in the study. For analysis of test-retest reliability, the Turkish version of the KHQ scale was developed using the back translation method, and it was administered on the day of admission and again one week later. The Qualiveen and SF-36 questionnaires were administered to the patients for validity analysis. Moreover, the results of KHQ that had been administered to 35 patients with SCI were compared with those of 57 patients with MS. RESULTS: Both the internal consistency (Cronbach’s alpha coefficient: 0.68–0.93) and the test-retest reliability (intraclass correlation coefficient: 0.69–0.94) of the KHQ in patients with SCI were found to be high. Although a weak correlation between the subscales of the KHQ and SF-36, a moderate correlation between the subscales of KHQ, and the Qualiveen questionnaire (0.34<r<0.76, p<0.05) were found. The comparison of patients with SCI and patients with MS in terms of KHQ revealed that patients with SCI had significantly higher scores in some of the subscales of KHQ (p<0.05). These higher scores represented the worst health state, and the uppermost limit was determined as 100 points. CONCLUSION: The KHQ scale is an internally consistent, reliable, and valid scale for people with SCI. In addition, bladder-related quality of life was poorer in patients with SCI than in MS patients.